PENANGGULANGAN BENCANA KESEHATAN LINGKUNGAN DI DESA PASAR LAMA KECAMATAN SIMPANG EMPAT KABUPATEN BANJAR - Siti Mauliana Hairini; Anisa Damaiyanti; Fatur Rahman; Farid Syuhada; Hermeilia Sari; Putri Melyani; Windy Andrea Natali; Yuga Putra Ihenus (Wadah Inovasi Indonesia, 2022)
A clean environment is a very comfortable environment for all living things to carry out activities and benefit each other. The purpose of this service activity is to procure garbage bins, this work program is based on looking at the condition of schools in the village which still lacks organic and non-organic sorting trash cans and also the lack of awareness of the village community about the importance of maintaining health. The stages carried out in this service activity are the preparation stage and the procurement stage for garbage bins. This activity has good benefits for health, environment, socio-economics and preventing disasters in Pasar Lama Village, Simpang Empat District, Banjar Regency, disasters such as floods, dengue fever, soil pollution which can cause environmental pollution and cause various diseases. The benefit of the procurement of this garbage bin is that the village community is aware of the cleanliness of the environment and disposes of garbage according to the place provided.